1)(а-3)(а2-5а+10)
a^3-8*a^2+25*a-30
2) А) у(4x+3)-6(4x+3)
x*(4*y-24)+3*y-18
(4*x+3)*(y-6)
Б) yx-ya+3x-3a
(x-a)*y+3*x-3*a
(x-a)*(y+3)
3) (х-12)(x-3)-(x-1)(x-6)=6
(х-12)(x-3)-(x-1)(x-6) = -2 * (4x -15)
-2 * (4x -15) = 6
30 -8x = 6
-8x = -24
x = 3
4) А) 5в-вс-5с+с2
c^2+(-b-5)*c+5*b
(c-5)*(c-b)
Б) xb+by-ax-ay-3х-3у
(b-a-3)*y+(b-a-3)*x
(b-a-3)*(y+x)
5)
пусть а- ширина, тогда 3а-длина
площадь получается 3а^2 (s)
после изменения
(3а+2)(а+4)=S+78
раскрываем скобки и вместо S подставляем 3а^2
3а^2+12a+2a+8-78=0
14a=70
a=5 (ширина)
3а=15(длина)
1)=8а²(в²-9с²)=8а²(в-3с)(в+3с).
2)=2(х²-12ху+36у²)=2(х-6у)².
3)=-2а(4а4-4а²+1)= -2а(2а²-1)².
4)=5(а³-8в6)=5(а³-(2в²)³)=5(а-2в²)(а²+2ав²+4в4)
5)=(а³+а²)-(ав-а²в)=а²(а+1)-ав(1+а)=(а+1)(а²-ав)=а(а+1)(а-в)
6)=с4(а-1)-с²(а-1)=(а-1)(с4-с²)=с²(а-1)(с²-1)=с²(а-1)(с-1)(с+1).
1)=(х-у)²-7²=(х-у-7)(х-у+7)
2)=а²-(3в-с)²=(а+3в-с)(а-3в+с)
3)=(в³)²-(2в²-3)²=(в³+2в²-3)(в³-2в²+3).
4)=(m³+3³n³)+(m+3n)²=(m+3n)(m²-3mn+9n²)+(m+3n)²=(m+3n)(m²-3mn+9n²+m+3n).
5)=x²-y²+2x+4y-3=(x²+2x+1)-(y²-4y+4)=(x+1)²-(y-2)²=(x+y-1)(x-y+3).